The Christian-Muslim frontier : a zone of contact, conflict, or cooperation - Apostolov, Mario (RoutledgeCurzon advances in Middle East and Islamic studies, 2004)
An examination of the civilisational interface between Christianity and Islam from the unique perspective as a zone of contact rather than a distinct boundary.